PERUBAHAN POLA KEHIDUPAN KELUARGA DI ERA INDUSTRI - Hermawati Hermawati (Al Irsyad : Jurnal Bimbingan Konseling Islam, 2018)
The presence of industry with its various activities brings changes to the family both positive and negative. The influence of industry on family life can be seen in several ways, namely the change in the role of husband and wife, changes in family form, changes in family decision-making and also changes in the socialization process of family members.